Fabrication and characteristics of nitrogen-doped nanocrystalline diamond/p-type silicon heterojunction - Lu, D.; Li, H. D.; Cheng, S. H.; Yuan, J. J.; Lv, X. Y. (Nano-Micro Letters, 2010)
Nitrogen-doped nanocrystalline diamond films (N-NDFs) have been deposited on p-type silicon (Si) by microwave plasma chemical vapor deposition. The reaction gases are methane, hydrogen, and nitrogen without the conventional argon (Ar). The N-NDFs were characterized by X-ray diffraction, Raman spectroscopy, and scanning electron microscopy. The grain sizes are of 8∼10 nm in dimension. The N-NDF shows n-type behavior and the corresponding N-NDF/p-Si heterojunction diodes are realized with a high rectification ratio of 102 at ∼ 7.8 V, and the current density reaches to 1.35 A/cm2 at forward voltage of 8.5 V. The findings suggest that fabricated by CH4/H2/N2 without Ar, the N-NDFs and the related rectifying diodes are favorable for achieving high performance diamond-based optoelectronic devices.